2021
DOI: 10.1001/jamaoncol.2020.6982
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Outcomes of Virtual Care Across a Tertiary Cancer Center During COVID-19

Abstract: IMPORTANCE The coronavirus disease 2019 (COVID-19) pandemic has burdened health care resources and disrupted care of patients with cancer. Virtual care (VC) represents a potential solution. However, few quantitative data support its rapid implementation and positive associations with service capacity and quality. OBJECTIVE To examine the outcomes of a cancer center-wide virtual care program in response to the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTS This cohort study applied a hospitalwide agile se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 12 publications
6
105
1
Order By: Relevance
“…There is documentation of the implementation of a virtual care program at a highvolume cancer center that was feasible, maintained care quality and outpatient caseloads and had a high satisfaction among patients and physicians [75]. Loree and colleagues carried out an international Internet-based cross-sectional survey of 381 participants between April and June 2020 that evaluated patients' perspective and satisfaction with virtual appointment.…”
Section: Teleoncology Covid-19 and Breast Cancermentioning
confidence: 99%
“…There is documentation of the implementation of a virtual care program at a highvolume cancer center that was feasible, maintained care quality and outpatient caseloads and had a high satisfaction among patients and physicians [75]. Loree and colleagues carried out an international Internet-based cross-sectional survey of 381 participants between April and June 2020 that evaluated patients' perspective and satisfaction with virtual appointment.…”
Section: Teleoncology Covid-19 and Breast Cancermentioning
confidence: 99%
“…Limited data exist, however, on the direct impact of telemedicine on key quality of care metrics [ 14 ]. Preliminary studies during the pandemic have demonstrated that telemedicine utilization in the context of oncology practice can be rapidly adopted [ 15 ], though patient and provider perspectives on its utility vary [ 16 19 ]. Historically, telemedicine in oncology practice has focused on delivery of care to underserved rural areas [ 20 22 ], augmentation of global oncology efforts [ 23 , 24 ], provision of palliative care [ 25 ], remote monitoring of symptoms and mental health [ 26 ], and facilitation of multidisciplinary coordination with radiology and pathology teams [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual healthcare has many benefits, including increasing safety for healthcare providers and patients by allowing for connectivity from a distance and increasing the accessibility for those who struggle to attend in-person appointments due to location or time constraints [33]. While the concept of virtual care is not new in oncology, the widespread delivery of virtual care increased significantly during pandemic to protect patients from COVID-19 infection [34]. Although most participants in our study wanted to include some form of video calls or telehealth into their cancer care, this was not a desirable option for all.…”
Section: Discussionmentioning
confidence: 99%